3D printing of multifunctional gradient bone scaffolds with programmable component distribution and hierarchical pore structure. (March 2023) - Guo, Weiwei; Jiang, Zhaoliang; Zhong, Honghao; Chen, Guopeng; li, Xinde; Yan, Hongru; Zhang, Cheng; Zhao, Li
Graphical abstract: Abstract: Functionally graded bone scaffolds (FGBSs) are increasingly encountered in clinical medicine, but it remains challenging to replicate the complexity and functionality of natural tissues. Herein, a method for fabricating novel bone scaffolds with gradients in ingredients and structure was proposed via the combination of extrusion-based 3D printing and foam templating. Alumina toughened zirconia slurry and ZrO2 foam cream were prepared as printing inks and both displayed printable shear-thinning properties. The multi-material monolithic filaments extruded by means of a static mixer were then programmed and deposited to achieve a smooth gradient among constituents. Notably, compositional gradient and bionic hierarchical structures were processed in one continuous step. Ultimately, it was verified that FGBSs manufactured by this modified forming process had component and structure differences at both ends and smooth gradients in the middle. Implementing this gradient in bioinspired scaffolds can potentially reduce strain mismatches and facilitate bonding with the natural bone.